2014
DOI: 10.1177/0145721714535992
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Acculturation and Diabetes Risk Among Urban Immigrant Latinas

Abstract: Purpose The purpose of this qualitative study was to understand how acculturation influences diabetes risk among urban, immigrant Latinas (Hispanic women). Methods Five focus groups were conducted with 26 urban, immigrant Latinas who were at high clinical risk for developing diabetes. The focus group sessions were audiotaped and transcribed verbatim. The authors independently analyzed transcripts using an inductive method of open coding, and themes were established by consensus among authors. Results All o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 35 publications
1
19
0
4
Order By: Relevance
“…18,19 Findings from formative research informed minimal modifications to the Spanish-language Group Lifestyle Balance program participant handouts to increase their cultural salience for the target population. 15,20,21 The 24-session intervention was delivered in Spanish by one promotora to four groups of between five and nine participants, with each session lasting approximately 90 minutes. A second promotora provided logistic support during ILI sessions such as weighing participants and distributing printed materials.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Findings from formative research informed minimal modifications to the Spanish-language Group Lifestyle Balance program participant handouts to increase their cultural salience for the target population. 15,20,21 The 24-session intervention was delivered in Spanish by one promotora to four groups of between five and nine participants, with each session lasting approximately 90 minutes. A second promotora provided logistic support during ILI sessions such as weighing participants and distributing printed materials.…”
Section: Methodsmentioning
confidence: 99%
“…39 Prior to modifying the GLB materials, we conducted formative research suggesting fast food and sugar-sweetened beverages as specific dietary targets prevalent in the target population. 12,40 In a qualitative study of Latinas with prediabetes, we identified social and cultural factors, such as changes in family roles and food preparation practices that participants believed to be related to their diabetes risk. 12 Based on these findings, we developed culturally-appropriate dietary self-monitoring tools and targeted messages about healthy behavior change in the Latino family context that were incorporated into the protocol.…”
Section: Methodsmentioning
confidence: 99%
“…12,40 In a qualitative study of Latinas with prediabetes, we identified social and cultural factors, such as changes in family roles and food preparation practices that participants believed to be related to their diabetes risk. 12 Based on these findings, we developed culturally-appropriate dietary self-monitoring tools and targeted messages about healthy behavior change in the Latino family context that were incorporated into the protocol. (Appendix 1) This process of adapting the GLB protocol was also informed by feedback on the intervention materials given by the promotoras.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Latino parents consider that providing food for their children is an important aspect of good parenting (58)(59)(60), but this value can promote childhood obesity. A study among Latino women at risk for diabetes reported that improved economic conditions since immigration facilitated access to "high status foods" but, unfortunately, a less healthy diet as well (61). Lower acculturation (as measured by linguistic status) in Latino mothers was associated with increased BMI in their children (62).…”
Section: T1d In Latino and Asian-american Youthmentioning
confidence: 99%